Layer-induced scattering attenuation and VTI anisotropy - NW Shelf Australia synthetic study - Pevzner, R.; Müller, T.; Bona, Andrej; Gurevich, B. (2014)
© 2014 SEG.Seismic attenuation and anisotropy in the overburden can significantly affect seismic image quality, including amplitudes of the target horizons. Therefore, understanding magnitudes, causes and spatial distribution of attenuation and anisotropy is important for seismic imaging and reservoir characterization. Thin layering can cause both scattering attenuation and anisotropy. These phenomena can only be significant, if there is a strong contrast in elastic properties between the layers. We present a case study from North-West Shelf of Australia, where presence of shallow stiffcarbonate layers can be responsible for deterioration of seismic data quality through both attenuation and anisotropy.